Pengaruh Konsentrasi dan Lama Perendaman Larutan Polyethylene Glycol 6000 terhadap Panjang dan Jumlah Daun Bibit Sengon (Paraserianthes falcataria L.) dari Benih yang Terdeteriorasi: The Effect of Concentration and Length of Soaking Polyethylene Glycol 6000 Solution on The Length and Number of Sengon Leaves (Paraserianthes falcataria L.) Seedlings from Deteriorated Seeds - Hasby, Muhammad Farhan; Triani, Nova; Sutini, Sutini (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2024)
Wood production in Indonesia continues to increase every year. Sengon plant propagation is done using seeds. The problem with the propagation of sengon plants in Indonesia is the lack of availability of prime sengon seeds. This research aims to determine the effect of concentration, soaking time, and the interaction between concentration and soaking time of Polyethylene Glycol 6000 (PEG 6000) on the length and number of leaves of deteriorating sengon (Paraserianthes falcataria L.) seedlings. The research was carried out in the greenhouse of the Faculty of Agriculture, Universitas Pembangunan Nasional “Veteran” Jawa Timur. This research used a two-factor completely randomized design (CRD) with twenty treatment combinations and three replications. The first factor is the concentration of Polyethylene Glycol 6000 (PEG 6000) which consists of 0% peg 6000; 10% PEG 6000; 15% PEG 6000; 20% PEG 6000; and 25% PEG 6000. The second factor is the soaking time which consists of 6 hours, 12 hours, 18 hours and 24 hours. Observations include the height and number of leaves of the seedlings. The results showed that giving a concentration of 15% PEG 6000 gave better results for seedling height and number of leaves. The soaking time for PEG 6000 for 12 hours gave better results for the height of sengon seedlings and the soaking time for 18 hours gave better results for the number of leaves. The combination of concentration and soaking time for PEG 6000 showed no real interaction.